The effects of BRL 34915 and nicorandil on electrical and mechanical activity and on 86Rb efflux in rat blood vessels - Weir, S W; Weston, A H (British journal of pharmacology, 1986)
The effects of the antihypertensive agent BRL 34915 on a variety of responses of the aorta and portal vein of the rat have been compared with those of nicorandil. On portal vein, BRL 34915 (0.01-50 X 10(-6) M) and nicorandil (0.1-500 X 10(-6) M) abolished spontaneous mechanical activity and reduced mechanical responses to noradrenaline (0.1-100 X 10(-6) M) and K+ (5-20 X 10(-3) M) but had little inhibitory effect on responses to K+ (40-80 X 10(-3) M). The onset of the reduced responses to noradrenaline was delayed by both agents. On portal vein, BRL 34915 (0.1-50 X 10(-6) M) and nicorandil (0.5-500 X 10(-6) M) abolished spontaneous electrical and mechanical activity, hyperpolarized the smooth muscle cells to a value close to their calculated potassium equilibrium potential and increased the 86Rb efflux rate coefficient. On aorta, BRL 34915 (0.2-0.8 X 10(-6) M) and nicorandil (8-32 X 10(-6) M) reduced mechanical responses to noradrenaline (0.001-1 X 10(-6) M) and K+ (5-20 X 10(-3) M) but had little inhibitory effect on responses to K+ (40-80 X 10(-3) M). On aorta, BRL 34915 (0.2-0.8 X 10(-6) M) increased the 86Rb efflux rate coefficient whereas nicorandil (8-32 X 10(-6) M) was without effect. It is concluded that the inhibitory actions of BRL 34915 on both aorta and portal vein result from the opening of membrane potassium channels. The resulting membrane shunt inhibits the effects of excitatory agents. The inhibitory effects of nicorandil result from a combination of the opening of potassium channels together with an additional, undefined action.